Analisis Hukum Peranan Pemerintah Daerah Dalam Pengelolaan Dan Pendayagunaan Hasil Hutan Di Desa Wasuamba Berdasarkan Peraturan Menteri Kehutanan Nomor P.88/Menhut-II/2014 Tentang Hutan Kemasyarakatan : Studi Kasus Di UPTD KPH Unit II Lasalimu Kabupaten Buton - AL Hiday Nur; L.M. Ricard Zeldi Putra; Burhan Burhan (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
Community Farmer Groups as agents of change, which lately have been more charged with the role of guarding and regulating the conversion of forest functions, this must receive attention and of course it is very appropriate if applying for a Community Forest Management Permit (Hkm) is seen as a priority that must be considered. both by the Forest Service, NGOs and the community in general. The inefficiency of community forest licensing services is due to several obstacles that have so far not been properly resolved. These obstacles are mainly related to the institutional mechanisms of the Regional Government, especially those in the UPTD KPH Unit II Lasalimu, which so far have not been designed as a public service institution. The main objective of this research is to find out the role of the local government in managing and utilizing forest products under Community Forest (HKM) status and to find out the efforts by the local government in following up on Ministerial Regulation P.88/Menhut-II/2014 concerning Community Forestry. This study uses a normative and empirical juridical approach.